Sexual dimorphism and ontogenetic variation in the head shape of two neighbouring populations of the common lancehead Bothrops jararaca (Serpentes: Viperidae) - Siqueira, Lucas Henrique Carvalho [UNESP]; Piantoni, Carla; Marques, Otavio Augusto Vuolo [UNESP] (Oxford University Press (OUP), 2024)
The head is the most important element in trophic ecology among snakes. Head shape is affected by several factors, both intrinsic, such as size and sex, and extrinsic, such as geographical variation. Often, different populations are subject to different environmental conditions that are reflected in different phenotypes adapted to local conditions. Here, we investigate sexual dimorphism, ontogenetic allometry and environmental effects on head shape in two populations of Bothrops jararaca. We have found a significant effect of sex and population, with females from the highland population having a large braincase region and a more arrow-shaped head. Size increase accounted for a considerable amount of variation in shape, but the coefficient of correlation diverged between populations. Sexual dimorphism in head shape was not found in juveniles, but the ontogenetic trajectory was non-parallel between populations. Rainfall was most associated with a larger snout and reduced braincase. In the genus Bothrops, except in early stages, females often grow faster and attain larger sizes than males, which might affect head shape. Also, possible differences in diet, behaviour and ontogenetic variations between populations might be a reasonable cause of specific allometric trajectories.
Keywords: allometry; environment; geographical variation; geometric morphometrics; pit viper